Eat like a girl : 100+ delicious recipes to balance hormones, boost energy, and burn fat - Pelz, Mindy (Hay House, LLC, 2024)
Mindy Pelz takes her fasting lifestyle framework, first introduced in "Fast like a girl," and demonstrates how certain foods can enhance the benefits. The recipes included accommodate both plant-based and omnivore diets. Includes meal plans for 30-day "fasting reset."